Adverse event potentially due to an interaction between ibrutinib and verapamil: a case report. (February 2016) - Lambert Kuhn, E.; Levêque, D.; Lioure, B.; Gourieux, B.; Bilbault, P.
Summary: What is known and objective: Ibrutinib is a recently approved oral anticancer agent with pharmacokinetics that is very sensitive to metabolic inhibition. We report a serious side effect of ibrutinib potentially attributable to interaction with the moderate CYP3A4 inhibitor verapamil. Case description: A patient with mantle cell lymphoma was admitted to our emergency department with severe diarrhoea. During a prescription review, the clinical pharmacist identified a potential drug interaction between ibrutinib and verapamil present in a branded combination product also containing trandolapril. Ibrutinib was discontinued for 5 days, and verapamil was stopped. Lercanidipine 10 mg daily was prescribed as an alternative antihypertensive drug. The patient was discharged after 3 days with symptomatic treatment for his diarrhoea. Three months later, the patient maintained control with ibrutinib and olmesartan, but without verapamil. What is new and conclusion: This is the first description of a serious side effect of ibrutinib likely due to an interaction with the CYP3A4 inhibitor verapamil. Prescriptions of ibrutinib must be carefully checked to identify possible interactions with CYP3A4 inhibitors and patients monitored accordingly.